Gospodarjenje z gozdovi, ogroženost in ohranjanje habitatov divjega petelina (Tetrao urogallus L.) v Kamniško-Savinjskih Alpah - Žnidaršič, Miha (Gozdarski vestnik, 1999)
Thirty six capercaillie leks are known in the Kamnik-Savinja Alps in the area of the Local unit Kamnik of the Slovenian Forest Service. They are mainly found in the Menina and Velika Planina mountains. During the past 40 years thenumber of active leks has fallen from 28 in 1960 to 10 in 1998, predominantly after 1980. In 1998 deserted leks or those with only a single male predominate, a worrisome fact in view of the last known optimal phase of population oscillations. We consider the main factors to be the degradation ofhabitats and the abnormal forest structure with too few old trees. With intensive forest management and frequent felling in predominantly privately owned woods at the Menina Planina mountain, pole stands are represented by 90 %. Of the 20 known leks in the area, 16 are deserted. At the Velika Planina mountain, where most of the forest is state owned, there has been lengthier forest management, the region is more remote and with lesser felling the forest structure is more natural with more than 20 % mature trees and approximately 50 % older pole stands. This and the serenity of the region enable the long term stability of the subpopulation of the 3 known active leks. After a minimum in 1982 the number of males at Velika Planina has now increased, conforming to the long term population oscillation.
Keywords: divji petelin; habitat; rastišča; razširjenost